A new hybrid electromagnetic actuator for a modified skyhook control strategy with energy reduction. (June 2020) - Ding, Renkai; Wang, Ruochen; Meng, Xiangpeng; Chen, Long
This paper puts forward a modified skyhook control strategy for the electromagnetic suspension to improve the dynamic performance of the vehicle body and coordinate the wheel vibration simultaneously. The influence of control parameters (skyhook damping coefficient and passive damping coefficient) on the vehicle dynamic performances is analyzed, and the optimal values are determined. In addition, a new type of hybrid electromagnetic actuator which integrates a linear motor and a hydraulic damper is proposed to guarantee the reliability of electromagnetic suspension, and implement the modified skyhook control strategy. The structure parameters of the linear motor are optimized when the hydraulic damper is taken as a design basis, and the prototype is produced. Since the hybrid structure exactly matches the "hybrid damping" of the modified skyhook control strategy, the linear motor simply imitates the skyhook damping, which reduces the power demand compared with the electromagnetic suspension only with a linear motor. Then, the double loop control system for the hybrid electromagnetic actuator is designed. The external loop with a combined filter is utilized to obtain the body absolute velocity for the desired skyhook damping force, and the internal loop controls the linear motor to track the desired force with current hysteresis control. Finally, a comparative bench test is conducted, and the test results verify the effectiveness and control effect of hybrid electromagnetic actuator.